Seizure outcomes and complications associated with stereoelectroencephalography versus subdural electrodes for invasive monitoring in epilepsy surgery: a meta-analysis - Muthiah, Nallammai; Reecher, Hope M.; Maroufi, Seyed Farzad; Mansouri, Alireza; Harford, Emily; Abel, Taylor J. (Frontiers in Neurology, 2025)
IntroductionApproximately 1.2% of people in the United States have epilepsy. Accurate identification of seizure origin is critical for clinical management. Yan et al. published a systematic review up to 2018 comparing SDE and SEEG (two invasive monitoring modalities) on clinical effectiveness and safety. However, meta-analysis was not performed, and multiple centers have published key SDE and SEEG data since 2018.MethodsWe performed an updated literature search from Yan et al., through June 2023, of studies on patients who underwent SEEG or SDE for seizure focus localization. Inclusion criteria were: (1) randomized control trial, prospective or retrospective cohort study, or case series >5 patients, (2) at least one patient who underwent seizure focus resection, (3) outcomes of either seizure freedom or complications. Meta-5analytic methods were utilized for data analysis.ResultsAn initial search resulted in 4,647 records; 81 studies were included, reflecting 3,482 SEEG and 2,816 SDE patients. Compared to SEEG, SDE exhibited similar operative time (164 vs. 185 min, p = 0.50), inpatient monitoring time (8.7 vs. 8.9 days, p = 0.81), and length of hospital stay (11.8 vs. 9.7 days, p = 0.17). Seizure foci were identified in 95.4% of SEEG patients and 91.9% of SDE patients (p = 0.25). A higher proportion of SDE patients underwent resective surgery (85.6 vs. 74.0%, p < 0.01). Overall, 8.0% of SEEG patients and 10.6% of SDE patients experienced adverse events (p = 0.22). Incidence of infection was higher for SDE (1.8%) than for SEEG (0.3%, p < 0.01). Overall, 62.7% of SEEG patients and 63.4% of SDE patients achieved seizure freedom (p = 0.87). Among studies which directly compared SEEG to SDE, there were no differences in seizure freedom attainment or overall morbidity.ConclusionSEEG and SDE are safe and effective modalities to localize seizure foci. SDE was associated with higher rates of subsequent resection, but infection rate was higher for SDE than SEEG.